(untitled) (diségno, 2022)
When I received for the first time the assignment of teaching Architectural Representation Techniques in 1996, I made a small handout with my course notes: for the cover I chose precisely Table 4 of Jean-Jacques Lequeu’s Architecture Civile. [read more]